2017
DOI: 10.1158/0008-5472.can-16-2922
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Manipulation of Helicobacter pylori Virulence Function by Host Carcinogenic Phenotypes

Abstract: Helicobacter pylori is the strongest risk factor for gastric adenocarcinoma, yet only a minority of infected persons ever develop this malignancy. One cancer-linked locus is the cag type 4 secretion system (cagT4SS), which translocates an oncoprotein into host cells. A structural component of the cagT4SS is CagY, which become rapidly altered during in vivo adaptation in mice and rhesus monkeys, rendering the cagT4SS nonfunctional; however, these models rarely develop gastric cancer. We previously demonstrated … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 28 publications
(29 reference statements)
2
22
0
Order By: Relevance
“…During in vivo infection, cag Y sequences may be rapidly altered, resulting in altered activity of cag TFSS, which could be attenuated or similar to the parental strain. Similar findings were observed in the strains isolated from humans . In addition to CagY, the protein structure of CagN and CagM was also characterized.…”
Section: Virulence Factorssupporting
confidence: 79%
See 2 more Smart Citations
“…During in vivo infection, cag Y sequences may be rapidly altered, resulting in altered activity of cag TFSS, which could be attenuated or similar to the parental strain. Similar findings were observed in the strains isolated from humans . In addition to CagY, the protein structure of CagN and CagM was also characterized.…”
Section: Virulence Factorssupporting
confidence: 79%
“…17 CagY was reported to play an important role modulating the translocation of CagA and NF-κB and therefore influence inflammation during gerbil infection. 18 During in vivo infection, cagY sequences may be rapidly altered, resulting in altered activity of cag TFSS, which could be attenuated or similar to the parental strain.…”
Section: The Cag Pathogenicity Islandmentioning
confidence: 99%
See 1 more Smart Citation
“…Loss of function of the T4SS during in vivo adaptation in mice and primate models is frequent and has been associated with recombination in cag Y. Suarez et al . demonstrated that upon chronic H. pylori infection, cag Y recombination could modulate T4SS function in humans and rodents, which may be important for a successful long‐term persistence of infection.…”
Section: Components Of the Cag Pathogenicity Islandmentioning
confidence: 99%
“…Loss of function of the T4SS during in vivo adaptation in mice and primate models is frequent and has been associated with recombination in cagY. Suarez et al 20 demonstrated that upon chronic H. pylori infection, cagY recombination could modulate T4SS function in humans and rodents, which may be important for a successful long-term persistence of infection. The mechanism of cagY alterations was different in human and gerbil isolates, with predominance of single base-pair mutations in human samples and addition/deletion of motifs in the gerbil reisolates.…”
Section: Type 4 Secretion System Componentsmentioning
confidence: 99%